The Symbolic Meaning of Mangulosi in Batak Toba Traditional Weddings: Roland Barthes' Semiotic Analysis - Mhd Agri Amri; Refelina Tabitasari; Endelina Miranda; Devina Sianturi; Ria Valentine Angela Manalu; Meisuri Meisuri (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study aims to analyze the symbolic meaning of the mangulosi tradition in Toba Batak traditional wedding ceremonies using Roland Barthes’ semiotic theory. This research employs a descriptive qualitative method, with data collected from visual media such as YouTube and TikTok, supported by informants familiar with Toba Batak culture. The findings reveal that meaning in the mangulosi tradition is constructed through three levels of signification: denotation, connotation, and myth. At the denotative level, mangulosi is understood as the act of giving ulos in a wedding ceremony. At the connotative level, ulos and the ritual process convey symbolic meanings such as blessings, protection, harmony, and the strengthening of social and kinship relationships. At the myth level, the tradition reinforces the cultural ideology that marriage is considered legitimate when it receives recognition and blessings from family and customary authorities. Quantitatively, the findings show that artifacts are dominated by visual connotative meanings (40%), while ritual actions emphasize non-verbal (30%) and verbal (20%) meanings. Therefore, the mangulosi tradition is not only a ceremonial practice but also a medium for preserving cultural identity and social values within the Toba Batak community.